THE EFFECT OF PROJECT BASED LEARNING ON STUDENTS’ LEARNING OUTCOMES ON INDONESIAN ECOLOGY AND BIODIVERSITY TOPIC - Alandita, Faizah; Lestari, Tuti; Muttaqiin, Arief; Arif, Khairil (SEMESTA: Journal of Science Education and Teaching, 2024)
This research was motivated by the low learning outcomes of students in science subjects at SMPN 4 Pariaman. For this reason, in the teaching process it is necessary to use appropriate learning models. One learning model that can be used is the Project Based Learning (PjBL) model. The aim of the research is to determine the effect of implementing the PjBL learning model on the learning outcomes of class VII students at SMPN 4 Pariaman in the subjects of Ecology and Indonesian Biodiversity. This research uses a quasi-experimental type of research with a non-equivalent control group design. The research population was class VII students of SMPN 4 Pariaman TP.2023/2024, with a purposive sampling technique. Class VII.1 was chosen as the experimental class and class VII.2 as the control class. The experimental class uses the PjBL model, while the control class uses the conventional model. The instruments used were observation sheets on the implementation of the PjBL model and objective test questions adapted to the KKTP on Indonesian Ecology and Biodiversity material. The data obtained was analyzed and prerequisite tests and hypothesis tests were carried out. The results of the posttest value hypothesis test using the t test show tcount of 8.13 and ttable 2.00. The data shows tcount > ttable so that H1 is accepted, meaning that there is a significant difference between the average posttest scores of experimental class and control class students after being given different treatment. It can be concluded that providing treatment by applying the PjBL model has an influence on student learning outcomes in Indonesian Ecology and Biodiversity Material for class VII SMPN 4 Pariaman.